Real-time multispectral fluorescence lifetime imaging using Single Photon Avalanche Diode arrays - Lagarto, João L. (Sci Rep, 2020)
Autofluorescence spectroscopy has emerged in recent years as a powerful tool to report label-free contrast between normal and diseased tissues, both in vivo and ex vivo. We report the development of an instrument employing Single Photon Avalanche Diode (SPAD) arrays to realize real-time multispectral autofluorescence lifetime imaging at a macroscopic scale using handheld single-point fibre optic probes, under bright background conditions. At the detection end, the fluorescence signal is passed through a transmission grating and both spectral and temporal information are encoded in the SPAD array. This configuration allows interrogation in the spectral range of interest in real time. Spatial information is provided by an external camera together with a guiding beam that provides a visual reference that is tracked in real-time. Through fast image processing and data analysis, fluorescence lifetime maps are augmented on white light images to provide feedback of the measurements in real-time. We validate and demonstrate the practicality of this technique in the reference fluorophores and in articular cartilage samples mimicking the degradation that occurs in osteoarthritis. Our results demonstrate that SPADs together with fibre probes can offer means to report autofluorescence spectral and lifetime contrast in real-time and thus are suitable candidates for in situ tissue diagnostics.